An innovative approach to monitor the chip formation effect on tool state using acoustic emission in turning - Choudhury, I.A.; Bhuiyan, M.S.H.; Nukman, Y. (Elsevier, 2012)
Chip formation in metal cutting is inevitable and has a remarkable effect on tool state and therefore on the tool life. The work presented here introduce a new technique to independently monitor the chip formation effect on the tool state. This his been done by separating the chip formation events from the rest of the frequencies of occurrences. A customized tool holder and sensor setup are designed and integrated with the conventional tool holder to capture the signals from chip formation independently during turning. The signals taken by acoustic emission (AE) sensor represent the effect of chip formation on the tool state. The frequencies remaining below the transient offset signal are mostly coming from the tool wear and plastic deformation of the workmaterial. It has been observed that the acoustic emission is more susceptible to entire occurrences in turning. The time domain signal and corresponding frequency response can predict the tool state effectively. From raw AE signals and their RMS values, the tool wear and plastic deformation are observed to increase with the increase of cutting speed, feed rate and depth of cut. However, the tool wear has been found to decrease with chip breakage even at higher cutting speed and feed rate, and this has been verified by measuring the tool wear. The chip formation frequency has been found to vary between 68.3 kHz and 634.83 kHz while the maximum intensity was observed at 97.7 kHz.